Exploring Bread Making: Developing an Interactive E-Module Based on a Project-Based Learning Model for Vocational High School Students - Sari, Seprika; Hasan Saragih, Abdul; Mursid, Mursid (LPPM STKIP Kusuma Negara, 2024)
This study aims to determine the feasibility of interactive e-modules based on project-based learning on bread material and the effectiveness of interactive e-modules based on project-based learning on bread material. This research method uses research and development (R&D) through the Borg & Gall research and development model and the Dick & Carey learning model. The study was conducted in class XI Culinary Arts, SMK Telkom 2 Medan. The results of the study showed that: (1) interactive e-modules based on PjBL on bread material developed based on validation from material experts were 98.33% or very feasible; (2) based on learning media experts were 93.84% or very feasible; (3) based on learning design experts were 90% or very feasible; (4) based on student field trials were 88.96% or very feasible; and (5) interactive e-modules based on PjBL on bread material developed based on N-Gain results on the difference in pre-test and post-test scores with a result of 0.38 were in the range of 0.2 <d <0.8 with a moderate level of effectiveness.